The Effect of ICT Qualification on Selection of Long Term Suppliers - Yazicioglu, Osman; Borat, Oguz (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Enterprises working in the field of Industry 4.0 or high technology should review the criteria they use when choosing the companies in the supply chain. Even in crisis situations like Covid-19, decision-making criteria should be revised to maintain the functionality of the supply chain. In this study, it has been shown that the importance of ICT competence in companies in the supply chain should be taken into consideration by the parent company and that the selection of firms will change by including it in multi-criteria decision-making processes. In addition to the classic criteria used in the current supply chain evaluation, ICT criteria and sub-criteria have taken into consideration. ICT competencies of companies selected as candidates for supply chain evaluation are at different levels. The level of ICT preferred by the decision-making parent firm is decisive and it is possible to express it analytically with multi-criteria decision-making methods. The parent company needs an agile information and communication network between itself and the supply chain to easily adapt to technological developments and not to be affected by a crisis. Considering the ICT knowledge, skills and competence of the companies to be included in the supply chain, changes the supply chain ranking prepared according to classical criteria.